Taboo on TV: gender, religion, and sexual taboos in transnationally marketed Turkish soap operas. Issue 13 (2nd September 2018) - Yalkin, Cagri; Veer, Ekant
ABSTRACT: This study illuminates the ways in which men and women consume soap operas as a means of reflecting on and discussing sociocultural taboos. Through interpretive research we examine the ways in which religion, sexuality and gender relations are depicted in popular Turkish soap operas and how these depictions are consumed in the Balkans and the Middle East. This study challenges the assumption that consumption of taboo discourses leads to active identity modification or public defiance. Instead, in-depth interviews and online ethnography reveal that consumption of soap operas that challenge local religious and gender norms provide a liminal space for discussing taboo topics. Firstly, the findings indicate that talking about taboo topics seen in soap operas enables consumers to speak about what they expect gender and religious norms to be. Secondly, consumers get their mediated understandings of what religion is through soap operas. Thus, rather than simply offering escape, soap opera consumption facilitates the discussion of taboo topics.